2017
DOI: 10.1007/s10681-017-2049-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci affecting intensity of violet flower colour in potato

Abstract: Anthocyanins occur in potato tuber skin and flesh, sprouts, leaves, stems and flowers. The goal of this study was to identify genomic regions and candidate gene alleles key for accumulation of anthocyanins in potato corolla in various quantities. QTL analyses were performed in two mapping populations segregating for flower colour intensity and candidate genes were identified on the basis of function and location (chalcone isomerase, chi; chalcone synthase, chs) or location (RNA-dependent RNA polymerase 1, RDR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The 1:1 segregation pattern for flower color in the DRH F 1 segregating population combined with a presence/absence phenotype imply the flower color is due to segregation of a single regulatory gene. If there had been a continuum of color or a more complex segregation pattern, a biosynthetic gene might have been a more likely cause, as Śliwka et al (2017) hypothesized in their study on flower color intensity. Genetic mapping revealed a significant QTL on the distal end of chromosome 10 which, when combined with previous reports that this region harbors the requisite F locus for flower color ( van Eck et al 1993 ), provides further support for this assertion.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 1:1 segregation pattern for flower color in the DRH F 1 segregating population combined with a presence/absence phenotype imply the flower color is due to segregation of a single regulatory gene. If there had been a continuum of color or a more complex segregation pattern, a biosynthetic gene might have been a more likely cause, as Śliwka et al (2017) hypothesized in their study on flower color intensity. Genetic mapping revealed a significant QTL on the distal end of chromosome 10 which, when combined with previous reports that this region harbors the requisite F locus for flower color ( van Eck et al 1993 ), provides further support for this assertion.…”
Section: Discussionmentioning
confidence: 92%
“…The 1:1 segregation pattern for flower color in the DRH F 1 segregating population combined with a presence/absence phenotype imply the flower color is due to segregation of a single regulatory gene. If there had been a continuum of color or a more complex segregation pattern, a biosynthetic gene might have been a more likely cause, as Sliwka et al (2017) hypothesized Figure 4 IGV image of sequencing coverage of the DRH F 1 bulk segregant and monoploid haplotypes sorted by flower color aligned to chr10:51,474,000..51,469,500 of DM PGSC v4.03 Pseudomolecules. (Note that DM is white-flowered.)…”
Section: Discussionmentioning
confidence: 96%
“…Finally, the synthesized anthocyanins will be transported to the vacuole by the MATE transporter (Gomez et al 2009 ). The genetic basis of the anthocyanin biosynthetic pathway has been studied in potatoes and identified several essential genes involved in this pathway (Jung et al 2009 ; Zhang et al 2009a ; Zhang et al 2009b ; Śliwka et al 2017 ; Laimbeer et al 2020 ). However, so far, only a few studies have been conducted to investigate the transcriptional dynamics of the identified vital genes between different colored phenotypes (Laimbeer et al 2020 ; Riveros-Loaiza et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the synthesized anthocyanins will be transported to the vacuole by the MATE transporter(Gomez et al, 2009). The genetic basis of the anthocyanin biosynthetic pathway has been studied in potatoes and identi ed several essential genes involved in this pathway(Jung et al, 2009;Zhang et al, 2009a;Zhang et al, 2009b;Śliwka et al, 2017;Laimbeer et al, 2020). However, so far, only a few studies have been conducted to investigate the transcriptional dynamics of the identi ed vital genes between different coloured phenotypes(Laimbeer et al, 2020;Riveros-Loaiza et al, 2022).…”
mentioning
confidence: 99%